Penentuan Tarikh Kematian Ibrahim Putera Rasulullah S.A.W. Daripada Perspektif Falak - Man, Saadan; Rodzali, Mohamad Zakuwa (Jurnal Fiqh, 2010)
In Islamic history, there were several accounts on the date of the Prophet Muhammad?s son death, Ibrahim, which referred to some different dates. However, it was recorded that the death of Ibrahim occurred at the same day of solar eclipse, i.e. the only sun eclipse occurred within the prophethood era of Muhammad. This fact has been unanimously agreed by Muslim historians and it is based on several sound hadiths. With the development of science and technology today, the actual date of the death of Ibrahim can be identified by reviewing the data of solar eclipse. This paper analyzes this issue and attempts at investigating the actual date of Ibrahim?s death according to the theory of solar eclipse and its datas. The datas on Ibrahim?s death were acquired by historical documentation. The datas were then analyzed by using Moon Calculator software to calculate the actual date of Ibrahim?s death. The study formulates that the year of Ibrahim?s death as narrated in the history is accurate, but the day and month are different from what are mentioned by the historical accounts. This difference is assumed to be influenced by the practice of al-nasi? in lunar calendar which was prevalent among Arab community at that time.